ChemInform Abstract: Synthesis of 1, 2, 3‐Triazolyl Nucleoside Analogues as Potential Antiinfluenza A (H3N2 Subtype) Virus Agents. Issue 28 (15th July 2014) - Elayadi, Hanane; Smietana, Michael; Vasseur, Jean J.; Balzarini, Jan; Lazrek, Hassan B.
Abstract First time, a catalyst system consisting of CuCl2, KI, and montmorillonite K10 is used in Huisgen [3 + 2] cycloaddition reactions.